ESTUDO DA ABORDAGEM DE "DESIGN FOR CONSTRUCTION" APLICADA A CONSTRUÇÃO CIVIL: REVISÃO CRÍTICA - Santos, Francielle Coelho; Câmara, Myrelle Yasmine de Freitas; Carvalho, Michele (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The design for X (DFX) is basically, a method used in order to attend the needs of products. Thus, this article presents a critical review of the development of design for construction approaches, through the methodology of a systematic review to obtain relevant research about the subject. To ensure quality and validity, peer-reviewed journal papers were considered for their excellence, so the search engines employed in this work were Scopus and Web of Science (WoS), over a period of ten years. Selected journals are classified as Q1 and Q2 in the Scimago Journal & Country Rank in the areas of engineering, construction and architecture (AEC). As a result, it was obtained a total of 26 articles from 18 selected journals, where the largest number of publications were in Journal of Construction Engineering and Management, with a total of 4 articles and Energy and Buildings, with a total of 3 articles. Thus, it can be concluded that the concept of DFX is still little known and barely applied to civil construction, since most of the articles found with this keyword are related to the development of a product, and not specifically about the perception of a building.